Analysis of the signal cross talk via CCL26 in the tumor microenvironment in osteosarcoma - Masanori Kawano (Nature Portfolio, 2021)
Abstract Interaction with surrounding healthy cells plays a major role in the growth and metastasis of osteosarcoma. In this study, we hypothesized that humoral factors, which do not require direct contact with cells, are involved in the interaction between osteosarcoma and the surrounding cells. We identified the humoral factor involved in the association between tumor cells and surrounding normal cells using a co-culture model and investigated the significance of our findings. When human osteosarcoma cells (MG63) and human mesenchymal stem cells (hMSCs) were co-cultured and comprehensively analyzed for changes in each culture group, we found that the expression of chemokine (CC motif) ligand 26 (CCL26) was significantly enhanced. We also analyzed the changes in cell proliferation in co-culture, enhanced interaction with administration of recombinant CCL26 (rCCL26), reduced interaction with administration of anti-CCL26 antibodies, changes in invasive and metastatic abilities. CCL26 levels, motility, and invasive capability increased in the co-culture group and the group with added rCCL26, compared to the corresponding values in the MG63 single culture group. In the group with added CCL26 neutralizing antibodies, CCL26 level decreased in both the single and co-culture groups, and motility and invasive ability were also reduced. In a nude mice lung metastasis model, the number of lung metastases increased in the co-culture group and the group with added rCCL26, whereas the number of tumors were suppressed in the group with added neutralizing antibodies compared to those in the MG63 alone. This study identified a possible mechanism by which osteosarcoma cells altered the properties of normal cells to favorably change the microenvironment proximal to tumors and to promote distant metastasis.